Variabel Mediator dan Moderator dalam Penelitian Psikologi Kesehatan Masyarakat - Urbayatun, Siti; Widhiarso, Wahyu (Jurnal Psikologi, 2012)
Many literatures in the field of public health psychology concerned to involve third phenomenon when explain the relationship of two phenomenon. The third phenomenon then formulated as a mediator or moderator variables. Both of these variables are not much utilized by researchers in Indonesia. One of the possibility cause an under utilization of mediator and moderator variables was a technical problem, such as analysis procedures. This paper explains an analysis procedure using a mediator and moderator variables. Terminology and research example using of both variables are introduced then followed by an analysis illustration on empirical data. The demonstration of the procedure in this paper is expected to be as a a guidance for researcher when develop research design and manage data analysis. Keywords: mediator variable, moderator variable, public health psychology